Rhodotorula species infections in humans: A systematic review. Issue 2 (17th October 2018) - Ioannou, Petros; Vamvoukaki, Rodanthi; Samonis, George
Summary: Background: Fungal infections by Rhodotorula species are increasingly reported in the literature and consist of bloodstream infections, especially in patients with central venous catheters (CVC), as well as central nervous system (CNS), ocular and other less frequent infections. Objectives: The aim of this systematic review was to record and evaluate all available evidence regarding infections by Rhodotorula species. Methods: Systematic review of PubMed (through 9 August 2017) for studies providing epidemiological, clinical, microbiological, as well as treatment data and outcomes of Rhodotorula species infections. Results: A total of 111 studies, containing data of 248 patients, were eventually included in the analysis. The most common Rhodotorula infections were those of bloodstream, CNS and ocular infections, as well as peritoneal dialysis‐associated peritonitis. Epidemiology of each type of infection was different, with the bloodstream ones being more common in patients with malignancy and CVCs, while those of the CNS were more common in patients with AIDS. Mortality was variable being higher in CNS infections. Amphotericin B remains the most common agent used for treatment, irrespectively of the infection site. Conclusions: This systematic review thoroughly describes fungal infections by Rhodotorula species and provides information on their epidemiology, clinical picture, microbiology, treatment and outcomes.